PEMANFAATAN TEMPE SEBAGAI KOMODITI LOKAL UNTUK PASAR GLOBAL - I Wayan Agus Rangga Saputra; Luh Eka Susanti; Anak Agung Ayu Arun Suwi Arianti (Sewagati, 2024)
Tempeh, one of Indonesia's traditional fermented foods, has great potential to become an international culinary commodity because of its high nutritional content and relevance to healthy and sustainable food trends. However, the main problems faced are the use of tempeh which is only processed into household food, lack of product innovation, and packaging that is not attractive for the global market. Small businesses also face problems with a lack of understanding of good marketing strategies. This community service aims to provide business actors and entrepreneurial students with an understanding of the potential of tempeh as a competitive local commodity in the global market. Hygienic production processes, high-quality fermentation methods, creative packaging and digital marketing techniques are taught to participants in this service. The methods used include technical training, live demonstrations and interactive discussions guided by expert speakers in the field of food technology. Participants are also trained to utilize digital platforms such as marketplaces and social media to expand market reach. The results of the service show that business actors are able to understand the importance of production and packaging standards to meet export requirements. Product innovations, such as crispy tempeh and energy balls, received a positive response as diversification that suits global market tastes. Digital-based marketing strategies also provide opportunities to reach global consumers. By overcoming these challenges, tempeh has great potential to compete in international markets as a superior local product in Indonesia.